Annona Squamosa: A Natural Approach to Treat Diabetes Mellitus - Ranjana (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
There are assorted number derived compounds have been used in treatment of diabetes to control blood sugar level, as the modern drugs have adverse side effects in human being. Annona squamosa possess varied medicinal properties including antidiabetic activity. The study emphasizes on evaluation of antidiabetic activities of petroleum ether leaves extracts (ASPE) of the plant on streptozotocin-induced diabetic rats and normal rats. The ASPE significantly reduced peak blood glucose (Gp30) and area under curve (AUC) in diabetic rats in oral glucose tolerance test (OGTT) and oral sucrose (OSTT) tolerance test, but there was more reduction of Gp30 value than ACU in OSTT. Thus, it can be suggested that the ASPE, has a hypoglycemic response so it could be used as a herbal supplement for the management of DM.